Melchiorre Allegra’s confession (1937). At the origins of the (public) mafia speech (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
Melchiorre Allegra was a Sicilian doctor. Arrested during a police operation, in 1937 he released a statement in which he described the structure, the affiliation rituals and the normative codes of the Sicilian mafia. The confession became known in January 1962, when the reporter Mauro De Mauro published it in the newspaper "L'Ora". This article examines the historical meaning of the document, outlining the context in which it was produced in the light of the most recent studies. Referring to the time of its publication, the paper assigns to the testimony a central role in the genesis of the public discourse of the mafia.